Islamic law in action authority, discretion, and everyday experiences in Mamluk Egypt / by Kristen Stilt. - Stilt, Kristen (Oxford University Press, 2012)
Taking a 'law in action' approach to the study of Islamic law through a focus on the activities of the muhtasib in medieval Cairo and Fustat, this book paints a clear picture of the practice of Islamic law at the time. Connecting theory and practice, it sheds new light on the lived experience of the legal system.
Keywords: Law -- Egypt -- History -- To 1500.; Trade regulation -- Egypt -- History -- To 1500.; Trade regulation (Islamic law) -- Egypt -- History -- To 1500.; Muḥtasib -- Egypt -- History -- To 1500.; Egypt -- History -- 1250-1517.